A Novel Extended Susceptible, Exposed, Infected, and Recovered Model with Surveys for Analysis of COVID-19 Pandemic in Rajasthan - Meena Malik; Chander Prabha; Punit Soni; Khushboo Bhardwaj; Anshu Arora (Indian Journal of Public Health)
The impact of COVID-19 on human life has been catastrophic. It is the greatest crisis that humankind has ever faced. It already caused over 21 million confirmed cases and 758,000 deaths as of July 2021. Modeling frameworks, underlying assumptions, available datasets, and the region/time frame being modeled, predictions are possible, but the projections might vary widely, making it difficult to rely on one model universally way. This article presents the prediction and forecasting technique for COVID-19, using the widely adopted susceptible–exposed–infected–recovered (SEIR) model. The modified SEIR model is presented to model the pandemic to represent an open system where the mass movement of the population is considered. Spreading patterns of the pandemic over time, in actual and as per the model, are compared to check the authenticity of the model.